Effet du zaï amélioré sur la productivité du sorgho en zone sahélienne - Philippe Bayen; Salifou Traoré; Fidèle Bognounou; Dorkas Kaiser; Adjima Thiombiano (VertigO)
Impact of improved zaï on the yield of sorghum in sahelian zone. The present study aims to show that the effect of the organic matter and water management with zaï soil restoration technique, could improve agricultural productions on degraded soils. For this purpose, a random block experimental design of Fisher was used to test the germination capacity, the growth and the yield of sorghum on degraded land following zaï hole size and organic input. Base on different levels of these two factors, this design is formed by 32 plots accounting for 8 factorial treatments (2 x 4) and 4 replications. The results showed a significant effect of the size of the zai hole, the type of organic materiel input on the germination capacity, the growth and the yield of sorghum. The grain yield is ranged from 383, 10 ± 32, 13 kg/ha in zai big hole associated with compost input to 5, 77 ± 1, 90 kg/ha in small hole without organic input. The big holes increased grain yields especially in compost input treatment whose yields were 25 % higher than in small holes. The zai system with big hole associated with compost input could stand the agriculture productions on degraded land in sahelian zone.